O augúrio no livro II da Eneida: a destruição de Troia e o destino de Eneias - Almeida, Felipe dos Santos (2011)
This work aims at studying the augury on Virgil s Aeneid Book II, the most important epic poem on Latin literature. Its focus points towards the auguries occurred to Aeneas through the dream about Hector, Panthus speech, Venus warning, Jupiter s omens and Creusa s shadow, looking towards the religious elements by which these auguries bind themselves. The destruction of Troy and Aeneas destiny are foretold on these episodes. Thus, we proposed to analyze such auguries based on theories which embrace the study of narratology, religion and Roman and Greek thinking inside the Roman culture basis tradition, religion and virtue. To better understand of the text and following analysis, we present a general translation from the original text related to the episodes mentioned above.